تحليل العلاقة بين مرتكزات الصيانة المنتجة الشاملة وانتجية المكائن : دراسة استطلاعية لآراء المدراء في الشركة العامة لصناعة الادوية و المستلزمات الطبية في محافظة نينوى - د. أكرم احمد الطويل; رياض جميل وهاب (PROSPECTIVE RESEARCHES, 2023)
The Research strives to analysis the Correlation between Pillars of the Total Productive Maintenance and Machines Productivity in the state Company for Producing Drugs and Medical necessities in Nineveh. The Pillars of Total Productive Maintenance have main role in achieving some goals and one of them is to of improve Machine productivity since the studies that takes the correlation between fundamentals of the (TPM) and productivity of the Machines, Especially in the Iraqi Environment are limited. The searchers have tried to implicate these dimensions in their research. The searchers try through this research to answer the follow questions: 1. Do the managers in the company under research have any idea about the concept and fundamentals of the total productive maintenance? 2. Do the managers in the company under research have any idea about concept machines productivity and the factors that effect on It ? 3. Do the managers in the company under research have a clear idea about the Relationship (Correlation Relationship and Effect) between fundamentals of the total productive maintenance and machines productivity? The Research has come up with the following conclusions: - There is a significant correlation between fundamentals of TPM and machine productivity in company under research. - There is a significant effect between fundamentals of the TPM in machines productivity in company under research.